How Can E-Marketing Deliver Competitive Advantage to the Pfizer Injectables Brand in Europe? - Mohandas, Abhilasha; Nofal, Hani; Azzouni, Rawand (2011)
This report is an outcome of three months worth of research that was conducted to answer a deceptively simple question: “How can e-marketing deliver competitive advantage for the Pfizer Injectables brand in Europe?” Before one begins to sift through the pages, it is incumbent on the writers to give the reader some perspective on the subject area in order to allow one to better enjoy the content of this report. To begin with, ‘Pfizer Injectables’ is the umbrella brand that covers all of Pfizer’s hospital-directed generic products; prime being generic injectables. It was decided very early on to adopt a top-down strategy; i.e. to make a proposal which the entire European region could use as a blueprint, and then, time permitting, pick up on country specific nuances.